Improving the Motility of a Scleral Shell prosthesis with an Acrylic Orbital Implant: A case report - Varsha Ignatious1, Umesh Y Pai2, Shobha J Rodrigues3, Thilak Shetty B5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Evisceration or enucleation of the eye may be performed due to ocular injury, cosmetic deformity, infection or malignancy. After the surgical management, orbital implants can be placed to improve the cosmetic appearance, improve the motility of the scleral shell prosthesis and restore the loss of orbital volume. Various type of orbital implants are available amongst which, the acrylic orbital implant has gained popularity, over the years, due to its limited complications. The following case report represents a 26 year old patient who underwent enucleation and had an existing scleral shell prosthesis. His chief concern was the motility of the prosthesis. The prosthetic rehabilitation was done with the help of an Acrylic Orbital implant and a customized scleral shell prosthesis.